The Efficiency of Infection Control Teams In Lowering Infections Linked To Healthcare: Systematic Review - Ismail , Moamen Abdelfadil; alotaibi , Maha sayil; moafa, Asma Mohammed Ali; aldossari , Mohammed rashed tiny; almutairi, Albandari ali mutab; Alshehri, Nadia Dafer Majdua; Almutairi, Norah Muqbil; Alotaibi, Maha Majeb; alharbi, Mead; Aldosari, Fahad Hamoud; Alshahrani , Saud Hussain; Almatroudi, Naief Saleh AbdulAziz; et al. (Journal of Ecohumanism, 2024)
Background: Healthcare-associated infections (HCAIs) are a major concern in medical facilities worldwide, with an estimated 7–10% of patients affected. Infection control teams (ICTs) play a crucial role in preventing these infections by implementing guidelines, conducting surveillance, and educating healthcare professionals. However, the effectiveness of ICTs, with or without infection control link nurses (ICLNs), in reducing HCAIs remains unclear. This systematic review evaluates the impact of ICTs on infection rates, mortality, and compliance with infection control practices in various healthcare settings. Methods: A systematic review of randomized controlled trials (RCTs) was conducted following PRISMA guidelines. Databases searched included PubMed, EMBASE, CINAHL, and Cochrane CENTRAL. Studies assessing ICTs with or without ICLN systems in inpatient hospitals, outpatient clinics, and long-term care facilities were included. The primary outcomes measured were HCAI incidence, mortality, and hospital stay length, while secondary outcomes included staff compliance and cost-related factors. Risk of bias was assessed using the Cochrane risk-of-bias tool, and meta-analyses were performed where possible. Results: Nine RCTs met the inclusion criteria, covering hospital wards, dialysis units, and nursing homes. Meta-analysis of three studies showed no significant reduction in HCAI incidence (RR = 0.65, 95% CI: 0.45–1.07, very low certainty). Mortality due to HCAIs remained unaffected (RR = 0.32, 95% CI: 0.04–2.69, very low certainty). However, ICTs with ICLNs significantly improved compliance with infection control practices (RR = 1.17, 95% CI: 1.00–1.38, moderate certainty). Limited evidence was available for hospital stay duration and cost-related outcomes. Conclusion: While ICTs, particularly with ICLN systems, enhance compliance with infection control measures, their direct impact on reducing HCAIs and mortality remains uncertain. The high risk of bias and heterogeneity in study designs highlight the need for high-quality research with standardized outcome measures to assess the effectiveness of ICT interventions in healthcare settings.